Traumatic Optic Neuropath: Is this the Ideal Management Protocol? - Ehtesham Ahmad Raushan; Alok Kumar (Asian Journal of Medical Research, 2019)
Background: The aim of this randomized prospective study was to evaluate the management protocol decided in the cases of Traumatic optic neuropathy.Subjects and Methods:All the cases with a diagnosis of Traumatic optic neuropathy were managed using medical management with the steroids and cases not responding were operated upon by transnasal trans sphenoidal optic nerve decompression and the results were evaluated.Results:Patients presenting early and those who were operated early in the course of their illness showed a better recovery. Conclusion: Early intervention and following a defined management protocol can help preventing the blindness in as many as 80% of the cases following the injury.